Computing polygon as a research tool in studying hardware-software platforms - Antonov, A.S.; Krysanov, Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
The Computing polygon installed at the Research Computing Center of Moscow University provides operative access by Internet to computing resources to perform small preliminary experiments and to choose an appropriate hardware-software platform. The polygon is used to design an optimal platform suitable to a specific class of problems, to test new cluster systems, and to train students in hardware-software applications. In this paper, various clusters of the polygon are compared on the basis of special test problems.